Methylprednisolone as a Novel Adjuvant Therapy for Acute Cholecystitis with Non-obstructive Jaundice: A Case Report - Ni Made Aryani; I Ketut Suryana (Archives of The Medicine and Case Reports, 2025)
Acute cholecystitis is a common inflammatory condition of the gallbladder, primarily caused by gallstones or infection. While jaundice is often associated with acute cholecystitis due to biliary obstruction, it can also occur without evidence of obstruction, posing a diagnostic and therapeutic challenge. This case report presents a patient with acute cholecystitis and non-obstructive jaundice who demonstrated a remarkable response to methylprednisolone therapy. A 25-year-old male presented with a three-week history of right upper quadrant abdominal pain, jaundice, nausea, gray-colored stools, and dark urine. Physical examination revealed icterus, right upper quadrant tenderness, and a positive Murphy's sign. Laboratory investigations showed elevated total and direct bilirubin levels, transaminitis, and an increased gamma-glutamyl transferase (GGT) level. Abdominal ultrasonography confirmed acute cholecystitis with sludge but no biliary obstruction. The patient was treated with intravenous fluids, antibiotics, and supportive care. On the fourth day of hospitalization, methylprednisolone (62.5 mg twice daily) was initiated due to persistent jaundice and transaminitis. The patient's clinical and laboratory parameters improved significantly following the initiation of methylprednisolone. In conclusion, this case suggests that methylprednisolone may be a valuable adjuvant therapy for acute cholecystitis with non-obstructive jaundice, particularly in cases with evidence of liver and bile duct inflammation. Further studies are needed to confirm these findings and establish the optimal dosage and duration of methylprednisolone therapy in this setting.